Analysis of V-Cycle Multigrid Algorithms for Forms Defined by Numerical Quadrature - Bramble, J. H.; Goldstein, C. I.; Pasciak, J. E. (SIAM journal on scientific computing, 1994)
The authors describe and analyze certain V-cycle multigrid algorithms with forms defined by numerical quadrature applied to the approximation of symmetric second-order elliptic boundary value problems. This approach can be used for the efficient solution of finite element systems resulting from numerical quadrature as well as systems arising from finite difference discretizations. The results are based on a regularity free theory and hence apply to meshes with local grid refinement as well as the quasi-uniform case. It is shown that uniform (independent of the number of levels) convergence rates often hold for appropriately defined V-cycle algorithms with as few as one smoothing per grid. These results hold even on applications without full elliptic regularity, e.g., a domain in $R^2 $ with a crack.